Acute liver damage and anorexia nervosa: A case report - Bridet, Lionel; Beitia Martin, Juan Jose; Cabriada Nuno, Jose Luis (Turkish Journal of Gastroenterology, 2014)
Abstract Anorexia nervosa is an eating disorder predominantly affecting young women and characterized by an intense fear of gaining weight and becoming fat. Liver injury with mild elevation of hepatic enzymes is a frequent complication, and steatosis of the liver is thought to be the major underlying pathology. However, acute hepatic failure with transaminase levels over 1000 u/L is a very rare complication, and the precise mechanism of the liver injury is still unclear. We report a case of a 35-year-old woman with a history of anorexia nervosa who developed acute liver damage with deep coma in relation to profound hypoglycemia. The treatment was hydration, correction of electrolyte and fluid imbalance, and gradual nutritional support to prevent refeeding syndrome. Our patient’s consciousness was significantly improved with the recovery of liver function and normalization of transaminase levels. Although the mechanism of pathogenesis is largely unknown, we discuss the two principal hypotheses: starvation-induced autophagy and acute hypoperfusion.